Clinical features & outcome of dengue cases at a tertiary care centre (Bangladesh Medical Journal Khulna, 2021)
Background: Dengue is a very common seasonal public health problem causing significant mortality every year. In 2019 an outbreak occurred in Bangladesh. Few new manifestations and multi organ involvement were found.Objective: The objective of the study was to see the clinical and laboratory manifestations and outcome of dengue fever in a medical college hospital.Methods: It was an observational study in a medical college hospital in Bangladesh. Study period was one year. The patients were confirmed cases of dengue. Apart from detailed clinical history, examination of patient, relevant investigations and follow up was done until discharge.Result: Total number of cases was 98. Out of them 62 (63.2%) were male and 36 (36.73%) were female. Fever was most common (100%) manifestation and duration of fever ranged from 5 to 8 days with a mean duration of 6.3 (± 1.0) days. Among other symptoms generalized body ache was most common (63, 64.3%). Generalized weakness was present in 60 cases (61.2% cases) Bleeding manifestations was present in 41 cases; abdominal manifestations were found in 11 cases. Blood for NSI was positive in 94 (95.9%) cases; most cases (71, 72.4%) became positive between 2nd to 4th day. Ninety (91.9%) cases developed thrombocylopcnia and it started at 5th day in 45 (45.9%) cases. Blood transfusion was given in 12 (12.2%) cases & Platelet transfusion was given in 3 (3.1%) cases. Complete recovery was in 96 (98%) cases and Death occurred in 2 (2.0%) cases.Conclusion: Bleeding was a dominant presentation. Some atypical manifestations like gastro intestinal features were also observed. These findings will help physicians in early diagnosis of dengue.Bang Med J Khulna 2020: 53 : 3-7